Modeling Aggregate Use of Fund Resources-Analytical Approaches and Medium-Term Projections - Ghosh, Atish (IMF Working Papers; Working Paper, 2007)
This paper presents two approaches to modeling the use of IMF resources in order to gauge whether the recent decline in credit outstanding is a temporary or a permanent phenomenon. The two approaches-the time series behavior of credit outstanding and a two-stage program selection and access model-yield the same conclusion: the use of IMF resources is likely to decline sharply. Specifically, credit outstanding is projected to decline from an average of SDR 50 billion over 2000?05 to SDR 8 billion over 2006?10. Stochastic simulations suggest that it is unlikely to be much higher. These results are based on WEO projections with a correction for historically-observed over-optimistic biases. Alternative scenarios assuming a weaker economic performance or a less benign global environment do not alter these results.